APPROACHES TO INNOVATION PROCESS MANAGEMENT AT MACROAND MICROECONOMIC LEVELS - Pavel L. Vangelast (Модернизация, инновация, развитие)
Though the words ‘innovation’, ‘business’, ‘management decisions’ and phrases formed from these terms have been used for many years already, this does not mean that Russia is following the innovation-oriented development line. The main reason for this is that the current approaches to the innovation process management at the macroand microeconomic levels have not been properly developed by experts in the theoretical aspect. The innovation process as a background for sustainable development of the social and economic system should be fundamentally manageable. There is a necessity to encourage development of innovative activities, to transform the activity into the innovativeness at the national level (into the ability of the society and the economy to produce and consume innovations without the active participation of the state), as well as the ability to transform innovative ideas into commercially successful products or processes. The articles conveys the author’s view to some methodic principles and approaches to the innovation process management at macroand microeconomic levels.